Love Language Expressions among Newlyweds and Long-Married Couples: Interpersonal Communication’s Perspective - Bahtiar, Hikmanisa; Hamzah A. Machmoed; Harlinah Sahib (Universitas Cokroaminoto Palopo, 2023)
The purpose of this research was to explore the dynamics of love language and the nature of interpersonal communication in encouraging healthy communication in marriage. The research employed a mixed-methods approach to investigate the love languages of newlywed and long-married couples. The sample used is nonprobability sampling, where the population consists of married individuals. Thus, a purposive sampling strategy was employed. For this reason, 64 married individuals from the Bone area were included in the research, divided into 32 newlyweds and 32 long-married couples, each in the Tanete Riattang Barat sub-district, where three of each marital length willingly participated in an in-depth interview. Descriptive and thematic analysis were the types of analysis employed. The findings revealed several key points. Firstly, there is a wide spectrum of love language expressions. Second,